Isolation of a yeast strain able to produce a polygalacturonase with maceration activity of cassava roots - Martos, María Alicia; Zubreski, Emilce Roxana; Combina, Mariana; Garro, Oscar Alfredo; Hours, Roque Alberto (2017)
The objective of the present study was the isolation of a yeast strain, from citrus fruit peels, able to produce a polygalacturonase by submerged fermentation with maceration activity of raw cassava roots. Among 160 yeast strains isolated from citrus peels, one strain exhibited the strongest pectinolytic activity. This yeast was identified as Wickerhamomyces anomalus by 5.8S-ITS RFLP analysis and confirmed by amplification of the nucleotide sequence. The yeast produced a polygalacturonase (PG) in Erlenmeyer shake flasks containing YNB, glucose, and citrus pectin. PG synthesis occurred during exponential growth phase, reaching 51 UE.mL-1 after 8 hours of fermentation. A growth yield (Yx/s) of 0.43 gram of cell dry weight per gram of glucose consumed was obtained, and a maximal specific growth rate (µm) of 0.346 h-1 was calculated. The microorganism was unable to assimilate sucrose, galacturonic acid, polygalacturonic acid, or citrus pectin, but it required glucose as carbon and energy source and polygalacturonic acid or citrus pectin as inducers of enzyme synthesis. The crude enzymatic extract of Wickerhamomyces anomalus showed macerating activity of raw cassava. This property is very important in the production of dehydrated mashed cassava, a product of regional interest in the province of Misiones, Argentina.